Is spirituality related to survival in advanced cancer inpatients in Korea?. Issue 6 (21st December 2017) - Shin, Dong Wook; Suh, Sang-Yeon; Kim, Sun-Hyun; Park, Jeanno; Yoon, Seok Joon; Kim, Yu Jung; Kang, Beodeul; Kwon, Jung Hye; Park, Youngmin; Park, Kwonoh; Hui, David; Kim, Hyeon Jeong; et al.
Abstract: Objective: Spirituality is what gives people meaning and purpose in life, and it has been recognized as a critical factor in patients' well-being, particularly at the ends of their lives. Studies have demonstrated relationships between spirituality and patient-reported outcomes such as quality of life and mental health. Although a number of studies have suggested that spiritual belief can be associated with mortality, the results are inconsistent. We aimed to determine whether spirituality was related to survival in advanced cancer inpatients in Korea. Method: For this multicenter study, we recruited adult advanced cancer inpatients who had been admitted to seven palliative care units with estimated survival of <3 months. We measured spirituality at admission using the Korean version of the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being (FACIT-sp), which comprises two subscales: meaning/peace and faith. We calculated a Kaplan-Meier curve for spirituality, dichotomized at the predefined cutoffs and medians for the total scale and each of the two subscales, and performed univariate regression with a Cox proportional hazard model. Result: We enrolled a total of 204 adults (mean age: 64.5 ± 13.0; 48.5% female) in the study. The most common primary cancer diagnoses were lung (21.6%), colorectal (18.6%), and liver/biliary tract (13.0%). Median survival was 19.5 days (95% confidence interval [ CI 95% ]: 23.5, 30.6). Total FACIT-sp score was not related to survival time (hazard ratio [HR] = 0.981, CI 95% = 0.957, 1.007), and neither were the scores for its two subscales, meaning/peace (HR = 0.969, CI 95% = 0.932, 1.008) and faith (HR = 0.981, CI 95% = 0.938, 1.026). Significance of results: Spirituality was not related to survival in advanced cancer inpatients in Korea. Plausible mechanisms merit further investigation.